Eternal scars physical & emotional child abuse - Friedman, Gayle; Friedman, Gayle; Weber, Amy S. (New Jersey : Meridian Education Corporation, 2000)
This video is view about the effect of child abuse traumatic and long-lasting. Explores and dissects the signs and effects of child abuse, including mental, physical and sexual abuse.
Executive producers, Twilla Sears and Amy S. Weber; editor, Jodi Gonska
Narrator: Charlotte Angel
Keywords: Child Abuse